Отчего у зайца длинные уши: [сказки] / художники И. и В. Пустоваловы - Пустовалова Ирина (Читаем сами, 2015)
Экземпляры: 6 (20170921) / Инвентарный номер: 49704 / Цена: 70.00 / Авт.знак: О-88 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6